2021
DOI: 10.1038/s41598-021-86891-y
|View full text |Cite
|
Sign up to set email alerts
|

Deep anomaly detection of seizures with paired stereoelectroencephalography and video recordings

Abstract: Real-time seizure detection is a resource intensive process as it requires continuous monitoring of patients on stereoelectroencephalography. This study improves real-time seizure detection in drug resistant epilepsy (DRE) patients by developing patient-specific deep learning models that utilize a novel self-supervised dynamic thresholding approach. Deep neural networks were constructed on over 2000 h of high-resolution, multichannel SEEG and video recordings from 14 DRE patients. Consensus labels from a panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…is method makes the quantitative analysis of risk assessment more accurate and objective, and the model has achieved good results with five cases. e bidding cost of EPC projects is high, accounting for about 5% of the total contract cost, and good risk management in the bidding stage can help the general contractor save and reduce the pressure of risk management in the later contract negotiation and performance stages [8]. Zhang et al pointed out that the study of organizational structure mainly refers to the aspects of the composition of the organization and the relationship between the members of the organization [9].…”
Section: Related Workmentioning
confidence: 99%
“…is method makes the quantitative analysis of risk assessment more accurate and objective, and the model has achieved good results with five cases. e bidding cost of EPC projects is high, accounting for about 5% of the total contract cost, and good risk management in the bidding stage can help the general contractor save and reduce the pressure of risk management in the later contract negotiation and performance stages [8]. Zhang et al pointed out that the study of organizational structure mainly refers to the aspects of the composition of the organization and the relationship between the members of the organization [9].…”
Section: Related Workmentioning
confidence: 99%
“…In the medical domain, multimodal data are often complementary with each other, meaning that each type of data (e.g. images, sensor data, text report) can be used to extract unique latent representations to allow a better understanding of a pathology [160] 2021 Predictive Seizure Forecasting Private 3 Saeed et al [161] 2021 Multiple Multiple HHAR [144], MobiAct [147], MotionSense [149], UCI HAR [146], HAPT [162], Sleep-EDF [131], MIT Driver DB [163], WiFi CSI [164] 4 Spathis et al [165] 2021 Predictive (HR forecasting) Subject Health Private 5 Thiam et al [166] 2021 Generative Pain Classification BioVid heat pain [167], SenseEmotion [168] 6 Das et al [169] 2022 Predictive Stuttering prediction Private 7 Deldari et al [170] 2022 Contrastive (COCOA) Multiple UCI HAR [146], SLEEP-EDF, PAMAP2 [171], WE-SAD [87], Opportunity [172] 8 Lemkhenter et al [173] 2022 Predictive (PhaseSwap)…”
Section: Discussion and Open Challengesmentioning
confidence: 99%
“…Leveraging a combination of EEG and facial activity data extracted from video, Das et al [169] trained an explainable AI model to predict upcoming speech stuttering. Also, Martini et al [160] showed the potentiality of multimodal self-supervised learning by combining stereoencephalography (SEEG) and video data to forecast seizure events in drug resistant epileptic subjects.…”
Section: Multimodal Self-supervised Learning With Biosignalsmentioning
confidence: 99%
“…A popular type of RNN is LSTM, which is better at learning over longer periods of time than a vanilla RNN and has seen use in many CV algorithms. 26,30,44,59,64,66,67,68,69,70,71,72 (Continues)…”
Section: Rnnsmentioning
confidence: 99%